2016
DOI: 10.1186/s13099-016-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Serotype epidemiology and multidrug resistance patterns of Salmonella enterica infecting humans in Italy

Abstract: BackgroundSalmonella enterica is the zoonotic agent most frequently responsible for foodborne infections in humans worldwide. In this work the presence of S. enterica was investigated in 734 unique enteropathogenic isolates collected from human patients between 2011 and 2012.ResultsAll Salmonella spp. isolates were subjected to serotyping and antimicrobial susceptibility testing. Isolates displaying phenotypes and antimicrobial susceptibility profiles different from the reference strains were genotipically cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
2
17
0
2
Order By: Relevance
“…Among the serovars isolated, S. typhimurium was the most common serovar followed by Salmonella oslo. Similar findings are being reported by studies in Italy by Frasson et al [25]and in Africa by Karuiki et al [26]of S. typhimurium being the most frequent serovar causing non-typhoidal salmonellosis. This is in contraindication to studies reported elsewhere in the country.…”
Section: Discussionsupporting
confidence: 88%
“…Among the serovars isolated, S. typhimurium was the most common serovar followed by Salmonella oslo. Similar findings are being reported by studies in Italy by Frasson et al [25]and in Africa by Karuiki et al [26]of S. typhimurium being the most frequent serovar causing non-typhoidal salmonellosis. This is in contraindication to studies reported elsewhere in the country.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings are being reported by studies in Italy by Frasson et al [25]and in Africa by Karuiki et al [26]of S. typhimurium being the most frequent serovar causing non-typhoidal salmonellosis. This is in contraindication to studies reported elsewhere in the country.…”
Section: Discussionsupporting
confidence: 88%
“…The aim of this study was to examine the presence of potential food pathogenic bacteria after the process of small-scale cheese production in Ondo state, Nigeria. [12,13].…”
Section: Discussionmentioning
confidence: 99%